More money than God hedge funds and the making of a new elite - Mallaby, Sebastian (Penguin Press, 2010)
Based on unprecedented access to the industry, including three hundred hours of interviews, economist/journalist Sebastian Mallaby tells the inside story of hedge funds, from their origins in the 1960s and 1970s to their role in the financial crisis of 2007-2009. Wealthy, powerful, and potentially dangerous, hedge fund moguls have become the It Boys of 21st century capitalism. Ken Griffin started out trading convertible bonds from his Harvard dorm room; Julian Robertson staffed his hedge fund with college athletes half his age; Paul Tudor Jones posed for a magazine photograph next to a killer shark; Michael Steinhardt was capable of reducing underlings to sobs. Finance professors have long argued that beating the market is impossible, yet drawing on insights from physics, economics, and psychology, these titans have cracked the market's mysteries and gone on to earn fortunes. Their innovation has transformed the world, spawning new markets in exotic financial instruments and rewriting the rules of capitalism.--From publisher description.